(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article presents an ecological analysis of the relationship between length and weight in populations of the Kushakevich stone loach (Iskandaria kuschakewitschi (Herzenstein, 1890)) found in the rivers of the Fergana Valley. According to the research findings, the relationship between fish length and weight corresponds to an isometric growth pattern. This result confirms that the fish populations inhabit ecologically favorable river ecosystems in the valley, with low levels of interspecific competition. Additionally, the study reports the first recorded occurrence of I. kuschakewitschi in the Kosonsoy River.